Analizar las capacidades para la innovación de una muestra de Pymes del Valle Del Cauca (2023)
The objective of this degree project is to analyze the innovation capabilities of a sample of 38 SMEs in the department of Valle del Cauca. To achieve this end, a characterization of the companies in the sector was first made, secondly, an instrument previously designed and validated in the framework research of this work was applied, with 58 questions that allowed to identify their position against five innovation capacities, thirdly, a descriptive analysis of the data obtained from the tool chosen for the sample was carried out.